2003
DOI: 10.1111/j.1944-9720.2003.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Textbook Activities: Keeping Pace with Second Language Acquisition Research

Abstract: Recent research in second language acquisition found that learners reached higher levels of achievement when grammar practice included the processing and negotiation of meaning. This study explored the degree to which certain textbook activities reflected the earlier findings. A typology of production activities — based on the degree to which the activities required learners to process meaning — was established. The activities for two grammar points from selected Italian elementary language textbooks were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…Therefore, all writing activities, exercises and drills identified in the textbooks were conceived as writing tasks. Moreover, to examine which activity types predominated in our sample, Paulston's () classification of language activities (later modified by Aski, ) was used. Paulston () proposed a classification of language learning activities which consisted of mechanical drills, meaningful drills, and communicative drills.…”
Section: The Studymentioning
confidence: 99%
“…Therefore, all writing activities, exercises and drills identified in the textbooks were conceived as writing tasks. Moreover, to examine which activity types predominated in our sample, Paulston's () classification of language activities (later modified by Aski, ) was used. Paulston () proposed a classification of language learning activities which consisted of mechanical drills, meaningful drills, and communicative drills.…”
Section: The Studymentioning
confidence: 99%
“…Bragger and Rice note that textbooks are used "for curriculum design, for lesson planning, as a basis for assessment, and perhaps too often, to define their [instructors'] approach to teaching" (p. 107). Several researchers have examined how various aspects of language are addressed in textbooks, including approaches to grammar (Aski, 2003;Fernández, 2011), cultural content (Chapelle; Gulliver, 2010), stylistic variation (Etienne & Sax, 2009), pragmatics (Nguyen, 2011, and fluency (Rossiter et al, 2010). However, apart from examinations of pronunciation-specific materials (Gorsuch, 2001), little attention has been given to how pronunciation is treated in general ESL textbooks.…”
mentioning
confidence: 99%
“…Grammatical study rarely goes beyond a handful of elements chosen mainly because of their frequent use in the language. Upon her investigation of textbook activities, Aski (2003) concluded that ''meaning, context, and function continue to take a back seat to traditional presentations and practice of grammar'' (p. 58). Likewise, Ellis (2002b), as well as Wong and VanPatten (2003), observed that the grammar instruction promoted in language textbooks is based primarily on an explicit description, followed by mechanical practice.…”
Section: Methodology and Theoretical Basis Of Current Textbooksmentioning
confidence: 99%